2016
DOI: 10.15252/embj.201593725
|View full text |Cite
|
Sign up to set email alerts
|

A PBX1 transcriptional network controls dopaminergic neuron development and is impaired in Parkinson's disease

Abstract: Pre-B-cell leukemia homeobox (PBX) transcription factors are known to regulate organogenesis, but their molecular targets and function in midbrain dopaminergic neurons (mDAn) as well as their role in neurodegenerative diseases are unknown. Here, we show that PBX1 controls a novel transcriptional network required for mDAn specification and survival, which is sufficient to generate mDAn from human stem cells. Mechanistically, PBX1 plays a dual role in transcription by directly repressing or activating genes, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 69 publications
4
95
0
Order By: Relevance
“…Recent studies in mice showed that PBX1 has important neurological functions as it is involved in the regulation of regional identity and laminar patterning of the developing neocortex and neurogenesis of the subventricular zone 45 46. In human, PBX1 is now known to be required for specification and survival of dopaminergic neurons 47. Overall, these data converge towards the conclusion that in humans, kidney, urinary tract, and brain development are sensitive to PBX1 gene dosage variations.…”
Section: Discussionmentioning
confidence: 64%
“…Recent studies in mice showed that PBX1 has important neurological functions as it is involved in the regulation of regional identity and laminar patterning of the developing neocortex and neurogenesis of the subventricular zone 45 46. In human, PBX1 is now known to be required for specification and survival of dopaminergic neurons 47. Overall, these data converge towards the conclusion that in humans, kidney, urinary tract, and brain development are sensitive to PBX1 gene dosage variations.…”
Section: Discussionmentioning
confidence: 64%
“…In plants, BEL1-like proteins function in a tandem complex with KNOX-type TFs to regulate numerous aspects of growth and development (Chen et al, 2003;Smith and Hake, 2003;Brambilla et al, 2007;Rutjens et al, 2009;Khan et al, 2012). Related genes from the TALE class in animals also control important processes of growth and differentiation (Machon et al, 2015;Marcos et al, 2015;Merabet and Galliot, 2015;Villaescusa et al, 2016). The physical interaction between KNOX and BEL1 proteins and its functional significance have been documented in numerous plant species (Bellaoui et al, 2001;Müller et al, 2001;Smith et al, 2002;Chen et al, 2003Chen et al, , 2004.…”
Section: Stbel5 a Mobile Signal Controlling Development In Potatomentioning
confidence: 99%
“…a). One such molecule is the pre‐B‐cell leukemia homeobox‐1 transcription factor (PBX1), which has been recently shown to directly induce Nrf1 gene expression (Villaescusa et al, ). Interestingly, at 30 dpi, nuclear PBX1 levels are reduced in EAE spinal cords by 51.7 ± 3.7% ( p = 0.0004) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…b). PBX1 has been recently shown to activate Nfe2l1 expression to promote neuronal survival (Villaescusa et al, ). Furthermore, those studies also revealed that both PBX1 and Nrf1 are absent in substantia nigra neurons from Parkinson's disease patients, suggesting an impaired PBX1‐Nrf1 pathway in neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%